Prevalence and intervention of preoperative anemia in Chinese adults: A retrospective cross-sectional study based on national preoperative anemia database. (June 2021) - Lin, Jie; Wang, Chao; Liu, Junting; Yu, Yang; Wang, Shufang; Wen, Aiqing; Wu, Jufeng; Zhang, Long; Sun, Futing; Guo, Xiaojun; Liu, Fenghua; Li, Hailan; et al.
Abstract: Background: Preoperative anemia is an important pillar of perioperative patient blood management. However, there was no literature comprehensively described the current situation of preoperative anemia in China. Methods: We conducted a national retrospective cross-sectional study to assess the prevalence and intervention of preoperative anemia in Chinese adults. Data were from the National Preoperative Anemia Database based on hospital administration data from January 1, 2013 to December 31, 2018. Findings: A total of 797, 002 patients were included for analysis. Overall, 27.57% (95% CI 27.47–27.67) of patients had preoperative anemia, which varied by gender, age, regions, and type of operation. Patients who were female, age over 60 years old, from South China, from provinces with lower per capita GDP, underwent operations on the lymphatic and hematopoietic system, with laboratory abnormalities were more likely to have a high risk of preoperative anemia. Among patients with preoperative anemia, 5.16% (95% CI 5.07–5.26) received red blood cell transfusion, 7.79% (95% CI 7.67–7.91) received anemia-related medications such as iron, erythropoietin, folic acid or vitamin B12, and 12.25% (95% CI 12.10–12.40) received anemia-related therapy (red blood cell transfusion or anemia-related medications) before operation. The probability of preoperative RBC transfusion decreased by 54.92% (OR 0.46, 95% CI 0.46–0.47) as each 10-g/L increase in preoperative hemoglobin. Patients with preoperative hemoglobin less than 130 g/L was associated with longer hospital stay and more hospital costs. Patients with severe preoperative anemia given iron preoperatively had lower intra/post-operative RBC transfusion rate, shorter length of stay and less hospitalization costs, but no similar correlation was found in patients with mild and moderate preoperative anemia and patients given erythropoietin preoperatively. Interpretation: Our present study shows that preoperative anemia is currently a relatively prevalent problem that has not been fully appreciated in China. More researches will be required to optimize the treatment of preoperative anemia. Funding: National Natural Science Foundation of China and the Logistics Support Department of the Central Military Commission.